The Influence of Interior Design on Consumer Decisions in Choosing a Cinema Building - Hani Indah Permatasari; Mulyadi Mulyadi (Institut Seni Indonesia Surakarta, 2021)
The global expansion of the film industry has an impact on the construction of cinema buildings, including in Indonesia. The construction of the cinema building must pay attention to the interior design, because the interior design will impact the comfort of visitors and create a desire to return at a later date. The purpose of this study was to determine if the interior design of a cinema influenced visitors' choice of a cinema building. According to the study results, the interior design of the cinema influences visitors' interest in choosing a cinema building, as well as what interior design factors influence them.